2003
DOI: 10.4049/jimmunol.170.3.1274
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Blockade of Macrophage Migration Inhibitory Factor Ameliorates Acute Experimental Autoimmune Encephalomyelitis by Impairing the Homing of Encephalitogenic T Cells to the Central Nervous System

Abstract: Macrophage migration inhibitory factor (MIF) is a cytokine that plays a critical role in the regulation of macrophage effector functions and T cell activation. However, its role in the pathogenesis of T cell-mediated autoimmune diseases, such as experimental autoimmune encephalomyelitis (EAE), has remained unresolved. In this study, we report that anti-MIF Ab treatment of SJL mice with acute EAE improved the disease severity and accelerated the recovery. Furthermore, the anti-MIF treatment impaired the homing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 53 publications
3
91
0
2
Order By: Relevance
“…Several investigators have suggested the use of anti-MIF therapy. [16][17][18] Our data support such a use in the potential treatment of patients with IP.…”
Section: Discussionsupporting
confidence: 67%
“…Several investigators have suggested the use of anti-MIF therapy. [16][17][18] Our data support such a use in the potential treatment of patients with IP.…”
Section: Discussionsupporting
confidence: 67%
“…The significance of MIF in the immune system is being recognized to an increasing extent. Clinically, MIF is emerging as a prospective target of therapy for human diseases primarily affecting immunity (35,(37)(38)(39)(40). On the other hand, a number of findings have revealed many functions of MIF that are not restricted to those carried out as part of the immune system (9 -12, 39, 41-44).…”
Section: Resultsmentioning
confidence: 99%
“…Controls were exposed to aerosol of PBS. In the antibody-based interventions, OVA-sensitized BALB/c mice received a daily dose of 12.5 lg/g of anti-MIF mAb (XIV.15.5) [21] or isotype control via i.p. route starting the day before the aerosol challenge.…”
Section: Sensitization and Challenge Protocolmentioning
confidence: 99%
“…Th1 conditions: IFN-c (100 ng/mL; PeproTech), IL-12 (10 ng/mL; PeproTech) and anti-IL-4 (20 lg/mL; 11B11); Th2 conditions: IL-4 (50 ng/mL; PeproTech) and anti-IFN-c (XMG1.2; 100 lg/ mL). The concentrations of recombinant MIF and anti-MIF (XIV.15.5) [21] were 100 ng/mL and 100 lg/mL, respectively. After 24 h of primary stimulation, IL-2 (20 U/mL) was added to the cultures.…”
Section: Cd4 + Th Cell Differentiationmentioning
confidence: 99%
See 1 more Smart Citation